2018
DOI: 10.3389/fmicb.2018.01716
|View full text |Cite
|
Sign up to set email alerts
|

Dietary l-arginine Supplementation Alleviates the Intestinal Injury and Modulates the Gut Microbiota in Broiler Chickens Challenged by Clostridium perfringens

Abstract: Our previous reports suggested that Dietary l-arginine supplementation attenuated gut injury of broiler chickens infected with Clostridium perfringens by enhancing intestinal immune responses, absorption and barrier function, but its effect on the gut microbiome of broiler chickens remains unclear. This experiment aimed at evaluating the effects of Dietary l-arginine supplementation on the gut bacterial community composition and function of broiler chickens challenged with C. perfringens. In total, 105 1-day-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 71 publications
8
78
2
Order By: Relevance
“…(2015) had reported in 21-day-old chickens infected with Campylobacter jejuni . A similar observation was also reported by Zhang et al. (2018) .…”
Section: Discussionsupporting
confidence: 91%
“…(2015) had reported in 21-day-old chickens infected with Campylobacter jejuni . A similar observation was also reported by Zhang et al. (2018) .…”
Section: Discussionsupporting
confidence: 91%
“…In turkeys, necrotic enteritis (NE) is caused by Clostridium perfringens (C. perfringens) anaerobic bacteria and their toxins, and it causes considerable economic losses in poultry farming [1]. In a post-mortem analysis, the disease manifests by strong inflammation and necrosis of the intestinal mucosa, which impairs nutrient absorption, weakens immune and antioxidant systems and, consequently, compromises growth performance and increases bird mortality [2][3][4]. Pathological changes associated with NE are also observed in parenchymal organs such as the liver, which can disrupt many biochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al [14,22] found that diets supplemented with Arg minimize the damage to intestinal villi and crypts caused by coccidiosis in broiler chickens. Zhang et al [3] demonstrated that higher levels of l-arginine in the diet improved intestinal barrier integrity and modulated gut microflora in chickens challenged with C. perfringens, producing a consortium that was like to that of healthy controls with higher counts of beneficial bacteria and reduced counts of harmful species. According to Zhang et al [16], Arg protects the intestinal mucosa by stimulating non-specific immunity, improving intestinal absorption and inhibiting C. perfringens colonization in broilers with inflammatory bowel disease.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors influence the composition of gut microbiota, such as host genetics [26], diet [27], medical treatment [28], and rearing conditions [29]. The previous studies had demonstrated the effects of diet [30], feed additive [31] on the gastrointestinal microbiota. Here we defined effects of in-feed chlortetracycline on chicken fecal community diversity and richness.…”
Section: Discussionmentioning
confidence: 99%